Long‐term sequelae in survivors of childhood leukemia with Down syndrome: A childhood cancer survivor study report. Issue 3 (3rd November 2017) - Goldsby, Robert E.; Stratton, Kayla L.; Raber, Shannon; Ablin, Arthur; Strong, Louise C.; Oeffinger, Kevin; Sklar, Charles A.; Armstrong, Gregory T.; Robison, Leslie L.; Bhatia, Smita; Leisenring, Wendy M.
Abstract : BACKGROUND: Children with Down syndrome (DS) are at increased risk of developing acute leukemia and are more prone to acute toxicities. We studied the incidence and severity of chronic health conditions among survivors of childhood leukemia with DS compared with those without DS. METHODS: Chronic health conditions reported by questionnaire were compared between 154 pediatric leukemia survivors with DS and 581 without DS, matched by leukemia, age at diagnosis, race/ethnicity, sex, radiation location and chemotherapy exposure using Cox models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Subjects were selected from 7139 5‐year survivors of leukemia in the Childhood Cancer Survivor Study. RESULTS: Risk of at least 1 late onset chronic health condition (grade 1‐5) was similar in the DS population compared with the non‐DS group (HR, 1.1; 95% CI, 0.7‐1.5). Serious chronic health conditions (grade 3‐5) were more common in DS survivors (HR, 1.7; 95% CI, 1.1‐2.6), as were ≥ 3 chronic health conditions (grades 1‐5) (HR, 1.7; 95% CI, 1.2‐2.4). The 25‐year cumulative incidence of any condition (grades 1‐5) was 83% for DS survivors and 69% for non‐DS survivors. CONCLUSION: Leukemia survivors with DS have therapy‐related chronic health conditions comparable to those of similarly treated survivors without DS, with a few notable exceptions: 1) an increased risk of cataracts, hearing loss, and thyroid dysfunction compared with survivors without DS (though these are known risks in the DS population), 2) decreased risk of second cancers, and 3) increased risk of severe or multiple conditions. Practitioners should be aware of these risks during and after therapy. Cancer 2018;124:617‐25. © 2017 American Cancer Society . Abstract : Matching Down syndrome (DS) leukemia survivors with non‐DS leukemia survivors based on leukemia type, age at diagnosis, sex, race/ethnicity, chemotherapy, and radiation exposure reveals no overall increase in risk of late onset chronic health conditions, including heart disease, and an increased risk for serious medical conditions typical for adults with DS, such as cataracts, endocrine abnormalities, and hearing loss. These results are similar to those for adults with DS and no leukemia, with a decreased incidence of secondary malignant neoplasms.